Assessment of intraepidermal nerve fiber densities in 5 µm sections from arm and leg – a search for normative age-related values - Ekman, Linnéa; Dahlin, Lars B.; Englund, Elisabet (Free Neuropathology, 2024)
Background and aims: Normative values are lacking regarding intraepidermal nerve fiber density (IENFD) in thin sections of 5 µm. Thus, we aimed to assess IENFD in thin sections in a healthy adult population as well as to investigate whether IENFD is related to age, sex, and site of excision. Methods: Archival skin biopsies or excisions at the Department of Pathology, Lund, Sweden, from arm and leg were collected, re-sectioned, and immunohistochemically stained for Protein Gene Product 9.5 during 2020–2023. Nerve fibers were manually quantified in the 5 µm thin sections, and IENFD was compared between age groups, sex, and excision sites. Results: IENFDs were evaluated in 602 samples from 591 healthy adults aged 18 to 97 years (295 women, 296 men). Median IENFD values are presented, stratified by age groups, sex, and excision sites. Higher IENFD was observed in the arm compared to the leg, as well as in the proximal compared to the distal leg, however not across all age groups. Levels of IENFD were lower among older adults, compared to all younger groups. Conclusion: We have presented data on IENFD in thin 5 µm sections from a healthy adult population. Despite differences in IENFD observed across age groups, sexes, and excision sites, no strong conclusions regarding affecting factors could be drawn except that individuals > 65 years present with lower IENFD. Additional research and development of the method are warranted.